The Determinants of Intent to Whistle-blowing: Organizational Commitment, Personal Cost of Reporting, and Legal Protection - Devi Safitri (Universitas Negeri Semarang, 2022)
Purpose : This research aims to empirically prove the intention to whistle-blowing influenced by organizational commitment, personal cost of reporting, and legal protection. The population studied was all employees who worked at the People’s Credit Bank (BPR) in Riau Province.Method : Sampling technique using purposive sampling method so that the quantity of samples as many as 27 People’s Credit Banks in Riau Province with 135 respondents to be sampled in accordance with the criteria set, but 90 questionnaires received and that can be processed. The study used quantitative data with primary data. The study used questionnaires with Likert scale measurements. Data analysis used is inferential data analysis using SEM with the help of WarpPLS software version 6.Findings : The results showed that the higher the commitment of the organization, the higher the intention of a person to do whistle-blowing. The study concluded that the organization’s commitment and high legal protections are able to increase the intention of employees to whistle-blowing. But the personal cost of reporting has not been able to show a negative influence on whistle-blowing intentions, due to the perception of personal costs of employees if reporting fraud there will be attention and protection from the organization’s management. Novelty : This study is different from previous research because it focuses more on discussing three factors of whistleblowing intentions, including organizational commitment, personal costs of reporting, and legal protection using the theory of prosocial organizational behavior and theory of planned behavior (TPB) in the scope of employees working at Rural Banks. (BPR) Riau Province. Keywords : Intention to do Whistle-blowing; Organizational Commitment; Personal Cost of Reporting; Legal Protection